Ch'aekkŏri painting a Korean jigsaw puzzle - Black, Kay E. (Sahoipyoungnon Academy, 2020)
Ch'aekkori refers to paintings of books, stationery, ceramics, incense burners, bronze ware and other items found on the bookshelves of scholars, painted on folding screens in the late Choson period. Paintings of this theme did not receive much attention in Korean art except for a small number of folk paining lovers and collectors until the 1970s. Fascinated by ch'aekkori during her first visit to Korea in the mid-1970s, the author Kay E. Black started studying the subject and received her master's degree in art history at University of Denver. Since then, she has vigorously devoted herself to research on ch'aekkori, visiting numerous collections in Korea, Japan, the U.S. and Europe and meticulously examining as many as 150 extant works. She also collaborated with the late Edward W. Wagner, formerly Professor of Korean history at Harvard and one of the foremost authorities on Korean genealogies, to identify ch'aekkori painters and their intricate family lineages. Their research discovered many of the pieces were painted by professional painters hired at the court, who were closely related in family lineages. More than thirty years of the author's research on ch'aekkori is summed up in this comprehensive study.